Women Living with HIV over Age of 65: Cervical Cancer Screening in a Unique and Growing Population - Alexandra Aserlind; Karla Maguire; Lunthita Duthely; Stefan Wennin; JoNell Potter (Hindawi Limited, 2017)
Objective. Women living with HIV are at increased risk of human papillomavirus (HPV) infection, which can lead to cervical cancer. New guidelines recommend indefinite screening. The objective of this study is to describe cervical cancer screening practices and colposcopy results in a cohort of women living with HIV over age of 65 who were followed before the new guidelines. Comorbidities, sexually transmitted infections (STIs), and other risk factors were evaluated. Methods. We conducted a retrospective chart review on 75 women aged 65 or older living with HIV with at least one Pap smear. Results. The mean age of the cohort was 66.5 and at HIV diagnosis was 56. The majority of women were immunocompetent. 80% had serial Pap smears. Of these, 86% of 238 were negative or ASCUS. No women progressed to HSIL. 92% of colposcopies had negative or CIN I results. Three women were treated successfully for high-grade dysplasia. More than half of women had other STIs. 72% were screened for HPV; 50% were positive. Conclusion. The majority of women had negative and low-grade Pap smears. Questions remain regarding the utility of continued Pap screening and the added value of HPV testing in this unique population of older women living with HIV.